Mutual Diffusion Driven NMR: a new approach for the analysis ofmixtures by spatially resolved NMR spectroscopy (2017)
We introduce a new approach for resolving the NMR spectra of mixtures that relies on the mutual diffusion of dissolved species when a concentration gradient is established within the NMR tube. This is achieved by cooling down a biphasic mixture of triethylamine and deuterated water below itsmixing temperature, where a single phase is expected. Until equilibriumis reached, a gradient of concentration, from‘pure’ triethylamine to ‘pure’ water, establishes within the tube. The amount of time required to reach this equilibrium is controlled by the mutual diffusion coefficient of both species. Moreover, a gradient of concentration exists for each additional compound dissolved in this system, related to the partition coefficient for that compound in the original biphasic state. Using slice selective experiments, it was possible to measure these concentration gradients and use them to separate signals from all the present species. We show the results acquired for a mixture composed of n-octanol, methanol, acetonitrile and benzene and compare themwith those obtained by pulse field gradient NMR.